Poverty strategy by extension of expanding creative economy - Suryanata, I Gusti Ngurah Putra (International research journal of management, IT and social sciences, 2018)
This study examines poverty reduction strategies by expanding the creative economy in Tohpati Village Klungkung, Bali. Poverty alleviation is a major problem in development in Bali and the quality of economic growth is the key to solving it. The main problems in poverty alleviation that must be faced today are related to the fact that economic growth is not spread evenly throughout the Bali region, this is evidenced by the high-income disparity between districts. Bali government has made a commitment to eradicating poverty in the context of implementing sustainable development, the government and all regional apparatus together with various elements of society bear the main responsibility for achieving sustainable development. The poverty alleviation program is not possible without good governance, as the basis for the implementation of sustainable development anywhere, including in Bali. By expanding the creative economic activities of the people poverty rates are expected to decrease from year to year. The problem in this research is how to implement programs that have been implemented by the government and the community to reduce poverty in Bali.